Gender Equality and Economic Growth in Brazil - Agénor, Pierre-Richard; Canuto, Otaviano (World Bank, Washington, DC, 2014)
This note studies the long-run impacts of policies aimed at fostering gender equality on economic growth in Brazil. After a brief review of gender issues in Brazil, this note describes a framework for quantifying the growth effects of gender-based policies in developing economies. The analysis is based on a computable overlapping generations (OLG) model that accounts for the impact of access to infrastructure on women's time allocation, as well as human capital accumulation, inter- and intra-generational health externalities, and bargaining between spouses. The model is calibrated for Brazil and is used to conduct two experiments, the first involving improved access to infrastructure, and the second a reduction in gender bias in the marketplace. The key lesson of these experiments, is that fostering gender equality, which may depend significantly on the externalities that infrastructure creates in terms of women's time allocation and bargaining power, can have a substantial impact on long-run growth in Brazil.